2016
DOI: 10.1002/jgm.2889
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic profiles and in vitro resistance to mitoxantrone and idarubicin in pediatric acute leukemias

Abstract: In AML, the resistance of blasts to idarubicin and mitoxantrone may reflect an impaired integrin pathway. In ALL, the development of resistance is caused by the inhibition of B and T cell activation. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Several studies have shown that the positive expression of ITGAM was closely associated with the prognosis of AML patients [20,21]. A previous study indicated that lncRNA ITGB2 was significantly associated with various immune signatures in AML [22]. Chemokines play an important role in tumor cell migration and infiltration of distant organ sites [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the positive expression of ITGAM was closely associated with the prognosis of AML patients [20,21]. A previous study indicated that lncRNA ITGB2 was significantly associated with various immune signatures in AML [22]. Chemokines play an important role in tumor cell migration and infiltration of distant organ sites [23].…”
Section: Discussionmentioning
confidence: 99%
“…Applying the collected expression and CGH microarray for analysis, some investigators pointed out that the ITGB2 gene may be one of the reasons why acute leukemia cells antagonize anthracyclines and are not sensitive to relevant chemotherapy regimens. In AML resistance of blasts to idarubicin and mitoxantrone may re ect impaired integrins pathway [29]. The high expression of ITGB2 in triple negative breast cancer affects the prognosis of patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…β2 was strongly up-regulated with down-regulated phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) in the AML profile. In AML, the resistance of blasts to idarubicin and mitoxantrone may reflect an impaired integrin pathway (Laskowska et al, 2016). Taken together, β2 is implicated in drug resistance and impaired integrin signalling.…”
Section: Integrin β2 (Itgb2 Cd18)mentioning
confidence: 99%